The effects of hormone replacement therapy combined with vitamins C and E on antioxidants levels and lipid profiles in postmenopausal women with type 2 diabetes - Naziroglu, M; Simsek, M; Simsek, H; Aydilek, N; Özcan, Z; Atilgan, R (Elsevier Science Bv, 2004)
Background: Recent studies have demonstrated that oxidative modification of low-density lipoprotein (LDL) involving the formation of lipid peroxides (MDA), exerts several biological effects that may contribute to the onset and progression of cardiovascular diseases in postmenopausal women with Type 2 diabetes (DPMW). Therefore, the aim of our study was to evaluate the effect of hormone replacement therapy (HRT), vitamin C and E (VCE) treatments on lipid profiles, glucose and MDA levels as well as antioxidant vitamins and enzymes in plasma and red blood cells (RBC) in diabetic or non-diabetic postmenopausal women (PMW). Methods: Oral HRT and VCE supplementation for 6 weeks were compared with HRT treatment in 40 non-diabetic PMW and 40 DPMW. Results: In the 40 postmenopausal women (PMW) and 20 postmenopausal women with DPMW who received oral HRT and 20 DPMW who received HRT plus VCE, there was a significant fall in MDA, total cholesterol, LDL-cholesterol and triglyceride values. Glyeated haemoglobin (HbA1c) in the DPMW was significantly improved with oral HRT and VCE although no significant change in white blood cell counts, vitamin A and HDL values occurred. Additionally, a fall in plasma glucose, HbA1c and platelet values also occurred in the PMW and DPMW groups by oral HRT and VCE treatments. There was a significant increase in plasma vitamin E and beta-carotene concentrations, catalase, glutathione peroxidase and reduced glutathione levels in RBC and plasma in DPMW by treatments with HRT and/or VCE. Conclusions: Daily VCE and HRT administrations both in PMW and DPMW seem to produce significant improvement in antioxidants concentrations, and the metabolic control of lipids and glucose. The HRT and VCE supplementations may strengthen the antioxidant defense system due to reducing blood glucose and lipid metabolites, and they may play a role in preventing cardiovascular diseases in postmenopausal women with Type 2 diabetes. (C) 2004 Elsevier B.V. All rights reserved.
21st Workshop in Macro and Micro Elements -- 2002 -- Jena, GERMANY
Keywords: oxidative stress; menopause; glycated hemoglobin; lipid peroxide; vitamins C and E